The Principles of Functioning of Acts by a Superior Requiring the Consultative Cooperation of Certain Persons (can. 127 § 2 CIC) - DZIERŻON, GINTER (Prawo Kanoniczne, 2013)
The author of the presented article out thorough interpretation of can. 127 § 2 CIC. The analysis he carried out shows that the legislator included in this regulation two hypotheses connected with the necessity for a superior to obtain the consent or counsel of certain persons. In his research the author proved that there different mechanism behind these two hypotheses. In the first, case, consultation in the form of consent is required. Therefore, a superior cannot make any intended acts without obtaining the consent of all the persons legally established as participants in the consultation. The counsel, on the other hand, functions in a slightly different way because in this hypothesis the opinion is obligatory but non binding. Despite such a nature of the counsel discussed in the analysed regulation, it remains an integrative component of a superior’s decision making process. The authority cannot confine himself to in the persons about his intended acts. This is because the persons are obliged to give their opinion on a specific regulation. A superior at the same time is obliged to asses their opinion regardless of his final decision.